Overcurrent Relay Coordination in a Grid-Connected Microgrid System - Avachat, Tanvi; Tibrewala, Saurabh; Barve, Rujuta; Swathika, O.V.Gnana (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Overcurrent faults are predominant in microgrid systems and high currents may cause damage to devices. Therefore, protection system for microgrids is required to isolate the devices from faults in the system. It is also critical to provide necessary primary and backup protection systems with proper time grading to isolate such faults. Overcurrent (OC) Relays are frequently used in microgrids and it is necessary to optimize the time multiplier setting (TMS) of relays, which in turn minimizes the time of operation of the relays. In this paper, Dual Simplex and Revised Simplex optimization techniques are used to optimize the TMS value of relays and thereby to achieve quick fault clearance. The optimized TMS values of relays are obtained using Dual Simplex and Revised Simplex methods.